Pilar Pérez. Archivos del Silencio. Estado, indígenas y violencia en Patagonia central, 1878-1941 (Palimpsesto, 2017)
Pilar Pérez. Archivos del Silencio. Estado, indígenas y violencia en Patagonia central, 1878-1941
Keywords: Pilar Pérez